Th17 Cells in Cancer: The Ultimate Identity Crisis - Bailey, Stefanie R.; Nelson, Michelle H.; Himes, Richard A.; Li, Zihai; Mehrotra, Shikhar; Paulos, Chrystal M. (Frontiers in Immunology, 2014)
Th17 cells play a complex and controversial role in tumor immunity and have been found to exhibit a fluctuating identity within the context of cancer. The recent, expanding literature on these cells attests to their puzzling nature, either promoting or suppressing tumor growth depending on the malignancy and course of therapeutic intervention investigated. This review addresses several newly appreciated factors that may help delineate Th17 cells’ immunological properties in the context of cancer. Several reports suggest that inflammatory signals induced in the tumor milieu regulate the functional fate and antitumor activity of Th17 cells. Recent findings also point to significant alterations in Th17 cells due to their interplay with regulatory T lymphocytes and cytotoxic CD8+ T cells within the tumor microenvironment. Finally, an appreciation for the stem cell-like properties of Th17 cells that augment their persistence and activity emerges from recent reports. The impact of these factors on Th17 cells’ antitumor efficacy and how these factors may be exploited to improve cancer therapies will be discussed.